Comparison of smith-petersen osteotomy, pedicular subtraction osteotomy, and poly-segmental wedge osteotomy in treating rigid thoracolumbar kyphotic deformity in ankylosing spondylitis a systematic review and meta-analysis. Issue 1 (December 2016) - Hu, Xumin; Thapa, Ashish; Cai, Zhaopeng; Wang, Peng; Huang, Lin; Tang, Yong; Ye, Jichao; Cheng, Keng; Shen, Huiyong
Abstract Background This study aimed to compare Smith-Petersen osteotomy (SPO), poly-segmental wedge osteotomy (PWO) and pedicular subtraction osteotomy (PSO) in patients with rigid thoracolumbar kyphosis primarily caused by ankylosing spondylitis. The efficiency, efficacy and safety of these three osteotomies have not been compared systematically, and no illness-oriented surgical type selection strategy for the treatment of ankylosing spondylitis related to non-angular kyphosis has been reported. Methods The inclusion and exclusion criteria were defined, and 19 electronic databases were searched for eligible studies without language limitations. For the included studies, data extraction, bias analysis, heterogeneity analysis and quantitative analysis were performed to analyze the correction of kyphosiskyphosis and the incidence of complications. Results Nine comparative studies that met the standards were included with a total of 539 patients that underwent SPO (n  = 120), PWO (n  = 119), or PSO (n  = 300). The correction of kyphosis by PSO was 8.74° [95 % CI: 0.7-16.78] greater than SPO. The correction of kyphosis by PWO was 13.88° [95 % CI: 9.25-18.51] greater than SPO. For local biomechanical complications, the pooled risk ratio of PWO to PSO was 1.97 [95 % CI: 1.03-3.77]. For blood loss, PSO was 806.42 ml [95 % CI: 591.72-1021.12] greater than SPO and 566.76 ml [95 % CI: 129.80-1003.72] greater than PWO. Conclusions To treat rigid thoracolumbar kyphosis, PSO showed higher efficiency and efficacy than SPO, and PWO had a higher efficacy than SPO. The risk of local biomechanical complications was greater in PWO than PSO. Bleeding was more severe in PSO than in SPO or PWO. The incidence of neural complications and systemic complications was similar.